2010
DOI: 10.3109/09638281003653302
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to work-ability for injured workers: literature review and comparison with available measures

Abstract: Components contributing to work-ability go beyond the ability to perform particular work tasks. Measures intended to be used to inform vocational rehabilitation arguably need to consider all these factors to maximise likelihood of a sustainable return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 45 publications
3
80
0
2
Order By: Relevance
“…As expected, and in line with the literature (e.g., Borella et al 2008;Camerino et al 2006;Müller et al 2013;Salthouse 2009;Schaie 1994;Schnitzspahn et al 2013), we found substantial age differences in subjective work ability and subjective health as well as in cognitive resources (i.e., crystallized intelligence, cognitive speed, short-term memory, working memory, and inhibition). Consistent with the predictions derived from the framework of Fadyl et al (2010), we also found substantial (positive) associations of a variety of specific cognitive functions with subjective work ability and health (particularly for shortterm memory, working memory, and inhibition). Importantly, these relations remained significant when controlling for age, education, depressive symptoms, and common self-regulation strategies, which does not argue in favor of those confounders being the major driving force in the relations observed.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As expected, and in line with the literature (e.g., Borella et al 2008;Camerino et al 2006;Müller et al 2013;Salthouse 2009;Schaie 1994;Schnitzspahn et al 2013), we found substantial age differences in subjective work ability and subjective health as well as in cognitive resources (i.e., crystallized intelligence, cognitive speed, short-term memory, working memory, and inhibition). Consistent with the predictions derived from the framework of Fadyl et al (2010), we also found substantial (positive) associations of a variety of specific cognitive functions with subjective work ability and health (particularly for shortterm memory, working memory, and inhibition). Importantly, these relations remained significant when controlling for age, education, depressive symptoms, and common self-regulation strategies, which does not argue in favor of those confounders being the major driving force in the relations observed.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, based on the framework of Fadyl et al (2010), we predicted that cognitive resources are related to work ability and health. In particular, regarding the role of specific cognitive abilities, based on the Action Regulation Theory (Hacker 2003; see also e.g., Kohn and Schooler 1983), we predicted that better cognitive functioning in crystallized intelligence (in terms of general knowledge) as well as in cognitive speed (as a general processing resource), in short-term memory, and in cognitively controlled higher-order functions such as working memory and inhibition (shielding current goals from distracting information) is substantially related to better work ability and health.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the difficulties encountered in attempts to meaningfully classify the various aspects highlight how much the actual practice of vocational rehabilitation involves situated, real--world processes of assessing and juggling resources, competing demands, interpersonal negotiations and the various other issues that arise in part because work carries such a significance for individuals and society [14]. This complexity is also problematic in the assessment of work--ability, as existing measures tend to be focused on generalities in the relationship between impairment and functioning rather than the specifics of the individual situation, despite these being very important [15]. Meaningful and robustly--developed standardised tools are essential because they enable useful comparisons between individuals, populations and programmes, as well as constituting resources that help practitioners such as health professionals collect relevant information that can enhance decision--making and actions [16,17].…”
Section: Introductionmentioning
confidence: 99%